Strength and workability characteristics of hybrid bamboo and steel fiber reinforced concrete. (2023) - Yogesh, P.; Ravi, Kumaresh; Karthik, R.; Bhavana, Modepu; Muthukumar, Surya; Sathyan, Dhanya
Abstract: Fiber-reinforced concrete (FRC) is a type of concrete that has random distribution of fibers to improve the structural integrity. The presence of fibers in concrete helps reducing cracks due to shrinkage, boost strength, enhance energy absorption, and at high temperatures they minimize severe spalling. FRC is available in many different types and quality, each with its own set of advantages. Steel fiber is one of them, which is an expensive material widely used in construction. Bamboo fiber, a green construction material, is utilized in several infrastructures as a Hybrid fiber reinforced concrete to improve the mechanical properties of concrete. This research was carried out to observe the properties of concrete like workability, split tensile strength, and compressive strength by varying proportions of bamboo and steel fibers in volume of concrete at 0%, 0.5%, 0.75% and 1.0%. According to the results from the study, it is found that hybrid fiber reinforced concrete can be a better alternative for plain cement concrete with significant increase in strength.